Communication & Society: A Critical Political Economy Perspective - Horst Holzer (tripleC: Communication, Capitalism & Critique)
This paper presents the English translation of one of Horst Holzer’s works on communication and society. Holzer elaborates foundations of a critical sociology of communication(s) that studies the relationship of communication and society based on the approach of critical political economy. He shows that such an approach relates communication and production, communication and capitalism; communication, ideology and fetishism; and situates communication in the context of social struggles for alternatives to capitalist social forms. The paper is followed by a postface in which Christian Fuchs contemplates why Holzer’s approach has been largely “forgotten” in the German social sciences and media and communication studies, in turn stressing the continued relevance of Holzer’s theory today.